Effect of Intermittent Ultrasonic Vibration-Assisted Compression on the Mechanical Properties of Zr-Based Amorphous Alloys - Lingyun, Yang; Shenpeng, Xu; Yan, Lou (Frontiers in Materials, 2021)
Bulk amorphous alloys have some good mechanical properties due to their special atomic arrangement and are now also popular materials in the field of materials. The Zr-based amorphous alloy has good mechanical properties, but it is different from the lattice slip materials with high ductility. When it is compressed and deformed, it will generate concentrated elastic force in the shear zone to make the amorphous instantaneous fracture. The properties of extremely poor plasticity make the Zr-based amorphous shortcomings prominent and difficult to use in engineering use. In this paper, it is found that the Zr-based amorphous alloy after the intermittent ultrasonic vibration-assisted compression (IUVC) can enhance its plasticity to a certain extent. Because the ultrasonic vibration stress of IUVC can increase the extra free volume of the Zr-based amorphous alloy, and increase the degree of "rejuvenation" of the amorphous alloy, which is manifested as an increase in plasticity. In order to explore how IUVC affects the plasticity of Zr-based amorphous alloys, this paper will design experiments to analyze the effect of different Intermittent time, pre-pressures and ultrasonic amplitudes on the plasticity of amorphous.